2015
DOI: 10.5797/jnet.tn.2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

A case of the direct carotid artery puncture in endovascular thrombectomy

Abstract: • Abstract • Objective: Endovascular thrombectomy may be a topic treatment in this year, because new evidences and increase in the number of cases will be expected. Elderly patients or arteriosclerosis patients often exhibited difficult access to the occlusive vessel, and it may lead to poor result. The direct common carotid artery puncture is an alternative method in cases of difficult access. Case presentation: A 90-year-old male presented with sudden-onset of the left hemiparesis. Magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In fact, we select direct puncture of the CCA when a catheter cannot be induced to the ICA in preoperative DSA. Direct puncture of the CCA is effective in cases where a transfemoral approach is difficult, and is performed in various endovascular treatments including acute revascularization, 6,7) carotid artery stenting, 8,9) and cerebral aneurysm coil embolization. 10,11) Angiospasm and vascular dissection have been reported as complications of direct puncture of the CCA, 7,10) although hematoma formation often becomes the primary issue in endovascular treatments that require antiplatelet drug administration or systemic heparinization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we select direct puncture of the CCA when a catheter cannot be induced to the ICA in preoperative DSA. Direct puncture of the CCA is effective in cases where a transfemoral approach is difficult, and is performed in various endovascular treatments including acute revascularization, 6,7) carotid artery stenting, 8,9) and cerebral aneurysm coil embolization. 10,11) Angiospasm and vascular dissection have been reported as complications of direct puncture of the CCA, 7,10) although hematoma formation often becomes the primary issue in endovascular treatments that require antiplatelet drug administration or systemic heparinization.…”
Section: Discussionmentioning
confidence: 99%
“…10,11) Angiospasm and vascular dissection have been reported as complications of direct puncture of the CCA, 7,10) although hematoma formation often becomes the primary issue in endovascular treatments that require antiplatelet drug administration or systemic heparinization. [6][7][8][9][10][11] When a hematoma forms around the CCA, dyspnea may arise from compression of the airway. Oshima et al 8) recommended direct puncture of the CCA under direct visualization by making a small incision rather than the percutaneous approach, to make certain of the puncture and hemostasis, and that a sheath is passed through the subcutaneous tissue to be fixed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] However, various factors might cause difficulties in guiding catheter (GC) induction, including the aortic arch structure, arterial tortuosity or calcification, and atherosclerotic stenosis. [9][10][11][12][13][14][15][16][17][18][19][20] Previous studies have indicated that the interval between treatment initiation and final recanalization had positive correlation with GC induction and favorable prognosis. 3,[9][10][11][12][13][16][17][18][20][21][22][23] For better prognosis, prompt change in approach route is necessary when difficulties are encountered in GC induction through the right common femoral artery (CFA), the most easily accessible artery during MT.…”
Section: Introductionmentioning
confidence: 99%
“…10,20 However, direct CCA puncture of the affected side is considered when GC induction remains despite changes in device and operator. 10,18,19 Additionally, RA puncture may be considered in patients with osteoarthritis, which leads to difficulties in extension from the fixed position. In addition, RA puncture might be also considered in patients undergoing dialysis with shunt vessel in the elbow.…”
mentioning
confidence: 99%
See 1 more Smart Citation